Open economy macroeconomics of commodity price fluctuation, sectoral inter-linkage and employment. Issue 6 (6th May 2020) - Basu, Moumita; Nag, Ranjanendra Narayan
Abstract : Purpose: This is a theoretical paper in the field of structuralist macroeconomics. The paper focuses on commodity price fluctuation which has emerged as one of the major macroeconomic factors with significant bearing on the relationship between the agricultural and nonagricultural sectors. Design/methodology/approach: The paper develops a dual economy model consisting of an agricultural sector and an industrial sector. The commodity price is subject to the fluctuations due to the fact that stock of primary goods is an asset which is sensitive to speculations. The paper considers a standard methodology of dynamic adjustment process involving change in stock of agricultural goods and price of agricultural goods under perfect foresight. The saddle path properties of the equilibrium are also examined. Findings: The paper shows that the balanced budget fiscal expansion, capital account liberalization and the agricultural expansion lead to expansion of the industrial sector as well as level of employment. The increase in world interest rate may lead to contraction of the industrial sector and depress employment. Originality/value: We will consider the openness of the economy in explaining how different macroeconomic policies and capital account liberalization generate multiple cross effects on the inter-connectedness between agricultural and the non-agricultural sector. The paper will discuss the issue of employment generation in conjunction with commodity price fluctuation. We depart from the literature by using Taylor rule under which interest rate is fixed by the Central Bank such that money supply becomes endogenous.